Pharmacists’ Involvement in Collaborative Practices in Anti-Retroviral Therapy Units of Five Governmental Hospitals in Addis Ababa - Alemseged Ayele Asfaw, Nahom Mulugeta Mamo, Samson Tadesse Molla, Segewkal Hawaze (Journal of Applied Pharmaceutical Science, 2014)
Improved chronic diseases management calls for teams with inter-professional collaboration. The study aims to assess pharmacists’ involvement in collaborative practice with physicians and nurses in anti-retroviral therapy units of five hospitals. Institution based cross-sectional survey with a sample size of 43 pharmacists, physicians and nurses, was conducted in May 2012. The response rate was 86.05% and involved 11 pharmacists, 6 physicians and 20 nurses. The role of the pharmacist was focused on dispensing and patient counseling. Consultation was given to other health professionals by 45.45% of the pharmacists but 54.54% of the pharmacists were not satisfied with their role. 72.72% of the pharmacist indicated collaboration on drug toxicities, side effects and on patient status with physicians and nurses; and rated their working communication and relation with physicians (72.72%) and nurses (81.81%) as ‘very good’. 36.36% of the pharmacists believed that there was no equitable decision making on patient cases. 84.62% of the physicians and nurses rated their collaboration with ART pharmacists as ‘good’ and ‘very good’. Overall, pharmacists’ involvement in collaborative practice with nurses and physicians was found to be a little bit engaging with the patient as compared to the traditional role despite the gaps that exist.
Keywords: Pharmacists, collaborative practice, Anti-retroviral therapy, physicians and nurses